(untitled) (Research, Society and Development, 2022)
Cervical Spondylomyelopathy or Wobbler Syndrome is characterized by dynamic and static compressions of the spinal cord and nerve roots that cause neurological and muscular signs, most commonly neck pain. The present study aimed to discuss the etiology, diagnosis, symptoms, pathophysiology, treatment and prognosis of cervical spondylomyelopathy in dogs. Google Scholar, PubMed and small animal medical and surgical clinic books. Data collection was carried out between September 2021 and February 2022, using the following search terms: “cervical spondylomyelopathy in dogs”, “wobblers syndrome”, and “spondylomyelopathy”, “cervical spondylomyelopathy treatment” covering modalities of: case reports and literature review, selecting studies from 1989 to 2022, in Portuguese and English. Canine Wobbler Syndrome is a recurrent neurological disorder in animals of large or giant breeds, mainly Dobermann pinschers, representing 80% of cases, in addition to the existence of reports in other breeds. It is therefore concluded that despite the uncertainties related to the etiology of Wobbler Syndrome, the relationship between this pathology and genetic factors of large dog breeds, such as Doberman pinscher, and the body conformation of certain breeds, such as Basset Hound, is relevant. Magnetic resonance imaging, although the test of choice, is rarely used for diagnosis, which implies the adoption of myelography associated with a previous examination of the cerebrospinal fluid as the most used method in the face of clinical suspicion, since the analysis of radiographs does not show enough information.